Determination of Watershed Characteristics and Curve Number (CN) for Ponnaniyaru Dam Catchment Area - R, Selvakumar; N, Nasir; C R, Suribabu (International Journal of Engineering and Technology, 2018)
In SCS-CN method, curve number is significant parameter in estimating runoff from the catchment of the reservoir or inflow to the reservoir. As this curve number is function of several parameters like hydrological soil group, LULC, land treatment, hydrologic conditions and AMC, the selection of CN for prediction of inflow to the lake or reservoir is considered as a crucial in the hydrological studies. LULC, micro-watershed, drainage density, and catchment slope are obtained using spatial analysis and also SCS Curve Number value for Ponnaniyaru dam catchment area is derived from the LULC data. Further, CN value is evaluated from actual rainfall data and runoff volume collected at the reservoir. The study reveals the significant variation of CN value among each event. The present case study highlights the sensitiveness of CN value in the computation of runoff from the watershed. Keywords: Curve number, LULC, AMC, drainage density.Â
Keywords: .